2021
DOI: 10.1155/2021/5023536
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin Dose-Dependently Modulates the Cell Senescence and Apoptosis of Gastric Cancer Cells

Abstract: Gastric cancer (GC) is the fourth most lethal cancer. Effective treatments are lacking, and our knowledge of the pathogenic mechanisms in play is poor. Oridonin from the Chinese herb Rabdosia rubescens exerts various anticancer activities. However, the dose-dependent effects of oridonin on human GC remain unclear. Here, we found that oridonin inhibited GC cell growth in a time- and dose-dependent manner. Low-dose oridonin induced GC cell cycle arrest at G0/G1 and cell senescence by suppressing the c-Myc-AP4 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Therefore, nding effective drug for the treatment of glioma is extraordinarily important. As a active diterpenoid and the main active factor of Rabdosia rubescens, ORI could inhibit multiple cancers include small cell lung cancer and gastric cancer [12,13]. However, the understanding about anti-glioma effect of ORI is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, nding effective drug for the treatment of glioma is extraordinarily important. As a active diterpenoid and the main active factor of Rabdosia rubescens, ORI could inhibit multiple cancers include small cell lung cancer and gastric cancer [12,13]. However, the understanding about anti-glioma effect of ORI is limited.…”
Section: Discussionmentioning
confidence: 99%
“…proteins (Gao et al, 2014). The anticancer influence of ORI is dosageand time-dependent pattern (Wang et al, 2021).…”
Section: Gastric Cancermentioning
confidence: 99%
“…It also induces G2/M‐phase cell cycle arrest by decreasing the expression of cyclinB1 and CDK1 proteins (Gao et al., 2014 ). The anticancer influence of ORI is dosage‐ and time‐dependent pattern (Wang et al., 2021 ).…”
Section: Ori Activity In Different Cancers In Vitro Studiesmentioning
confidence: 99%
“…Oridonin has previously been investigated for its therapeutic effects on the following types of caners: colon, 2 , 3 , 6 , 10 , 11 breast, 12 , 13 pancreatic, 14 , 15 lung, 16 , 17 , 18 gallbladder, 19 prostate, 20 ovarian, 21 oesophageal, 22 oral, 23 , 24 bladder, 25 liver 26 and other cancers. It has been reported that the inhibitory effect of oridonin on proliferation of gastric cancer is mainly related to inducing apoptosis and promoting autophagy, 27 , 28 , 29 without further in‐depth discussions. Our previous study found that oridonin can block the G 2 /M phase of gastric cancer cells 30 and induce apoptosis 31 by affecting the expression of cyclinD1/CDK4 and cyclinA/CDK2 proteins.…”
Section: Introductionmentioning
confidence: 99%